2021
DOI: 10.36679/kedokteran.v7i1.337
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kualitas Air Di Pesawat

Abstract: Asupan air yang cukup selama penerbangan merupakan hal yang penting untuk kesehatan dan kenyamanan kru dan penumpang. Risiko kontaminasi mikroba di air yang digunakan pesawat terbang oleh hewan atau kotoran manusia, dapat berasal dari sumber air bandara, terjadi saat kegiatan perpindahan air ke dalam pesawat, atau saat air disimpan di dalam pesawat. Pengukuran kualitas air di pesawat telah dilakukan oleh beberapa peneliti dan lembaga. Hal ini ditujukan untuk menilai seberapa bagus upaya penjagaan sanitasi air … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Research by [24] on orchid seeds indicated that ammonia content at a concentration of 63.7 mg/L stimulated growth and development, but higher concentrations gradually led to a decrease in germination, with total inhibition observed at 510 mg L −1 . Excessive ammonium accumulation beyond the requirements of seed metabolism can be toxic, impeding seed growth and development [25]. Ammonium toxicity results from the disruption of the cell membrane's charge gradient, allowing ammonia to penetrate the membrane and inhibit photophosphorylation [26].…”
Section: Komatsuna Seed Germination Under Different Combinations Of F...mentioning
confidence: 99%
“…Research by [24] on orchid seeds indicated that ammonia content at a concentration of 63.7 mg/L stimulated growth and development, but higher concentrations gradually led to a decrease in germination, with total inhibition observed at 510 mg L −1 . Excessive ammonium accumulation beyond the requirements of seed metabolism can be toxic, impeding seed growth and development [25]. Ammonium toxicity results from the disruption of the cell membrane's charge gradient, allowing ammonia to penetrate the membrane and inhibit photophosphorylation [26].…”
Section: Komatsuna Seed Germination Under Different Combinations Of F...mentioning
confidence: 99%